Copper Complexes of "Superpodal" Amine Ligands and Reactivity Studies towards Dioxygen - Jozwiuk, Anna; Uenal, E. Alper; Leopold, Stefan; Boyd, John P.; Haryono, Marco; Kurowski, Nadine; Escobar, Francisco Velazquez; Hildebrandt, Peter; Lach, Jochen; Heinemann, Frank Wilhelm; Wiedemann, Dennis; Irran, Elisabeth; et al. (European Journal of Inorganic Chemistry, 2012)
The results of studies focussed on copper complexes of a variety of ligands with an NN4 donor set are reported. The permethylated tetrapodal ligand 2 forms a complex with copper(I) which, upon reaction with dioxygen at 90 degrees C, yields a product having a bis(mu-oxido)dicopper(III) core (O-type product, 10), as inferred from UV/Vis and resonance-Raman spectroscopic data. The UV/Vis spectrum of 10 has two bands at 300 and 404 nm, with extinction coefficients of 9400 and 10400 L?mol1?cm1, respectively. Resonance-Raman spectra display two 16O/18O-sensitive bands which, based on the isotopic shifts and the absolute frequencies, are attributed to the CuO stretching modes of the O-type product. Complex 10 shows tyrosinase-like activity, as its reaction with sodium p-tert-butylphenolate at 90 degrees C in THF yields p-tert-butylcatechol, in an ortho-hydroxylation reaction (yield: 30?%). Two new rigid tetrapodal pentadentate ligands (the superpods 3 and 4) can be synthesized by condensation of the primary polyamine 1 with paraformaldehyde. Their copper(II) complexes (5 and 6) have been spectroscopically characterized. As ascertained by X-ray crystallography, 5 has the CuII ion in a tetragonal-pyramidal environment, with almost uniform CuN bond lengths (basal bonds: 2.052 angstrom and 2.070 angstrom; apical bond: 2.077 angstrom). No significant JahnTeller distortion is observed here. In 6, the ligand acts as a multinucleating donor, which leads to the formation of a ladder-like cluster of [Cu(mu 3-OH)] units containing a total of two ligands, six copper(II) ions, four hydroxido ligands and eight trifluoroacetate ions. Two of the trifluoroacetate ions are non-coordinating. Variable-temperature magnetic susceptibility data are reported for this hexanuclear copper(II) cluster. Copper(I) complexes of 1 and 3 have been characterized and allowed to react with molecular oxygen, which caused the decomposition of the complexes. The IR spectra of the oxygenation products have bands at 1652 and 1632 cm1, respectively, which are absent in the spectra of 1 and 3, suggesting that amine functions have been oxidized to imines.
Keywords: Tetrapodal pentadentate li-gands; Copper; Dioxygen; Tyrosinase-like activity; N ligands; Density functional calculations